If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -0.25(x + -8) + 0.5(x + 2) = x + 6 Reorder the terms: -0.25(-8 + x) + 0.5(x + 2) = x + 6 (-8 * -0.25 + x * -0.25) + 0.5(x + 2) = x + 6 (2 + -0.25x) + 0.5(x + 2) = x + 6 Reorder the terms: 2 + -0.25x + 0.5(2 + x) = x + 6 2 + -0.25x + (2 * 0.5 + x * 0.5) = x + 6 2 + -0.25x + (1 + 0.5x) = x + 6 Reorder the terms: 2 + 1 + -0.25x + 0.5x = x + 6 Combine like terms: 2 + 1 = 3 3 + -0.25x + 0.5x = x + 6 Combine like terms: -0.25x + 0.5x = 0.25x 3 + 0.25x = x + 6 Reorder the terms: 3 + 0.25x = 6 + x Solving 3 + 0.25x = 6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + 0.25x + -1x = 6 + x + -1x Combine like terms: 0.25x + -1x = -0.75x 3 + -0.75x = 6 + x + -1x Combine like terms: x + -1x = 0 3 + -0.75x = 6 + 0 3 + -0.75x = 6 Add '-3' to each side of the equation. 3 + -3 + -0.75x = 6 + -3 Combine like terms: 3 + -3 = 0 0 + -0.75x = 6 + -3 -0.75x = 6 + -3 Combine like terms: 6 + -3 = 3 -0.75x = 3 Divide each side by '-0.75'. x = -4 Simplifying x = -4
| 10=4y-2y | | -5a-9=21 | | -.17(x-18)+6(.5)(x+2)=6(x+8) | | -.16666(x-18)+6(.5)(x+2)=6(x+8) | | 6y=-5(y+1) | | 12+(2-40)-6= | | 5x-5y=10 | | 2a^2-5=0 | | 3z-4=3z+2 | | -20y=da | | a+198=2(x+7)(x-3) | | 2x^4-16x^2+30=0 | | a+120=2(x+7)(x-3) | | -5x^2+9x+2=0 | | 5x-2=26-2x | | -18=-2n | | 6(2-t)-(3-4t)=4 | | 5(x+8)=2(x+6) | | 5(x-8)=2(x+6) | | -4=3x | | 2x-18=9x+2 | | 7p-11=-3p+7 | | -(7y+1)-(-6y-6)=-2 | | 4(x+1)+2(x+6)=3 | | 7n+24=32 | | 7n-24=42 | | 3x-45=889 | | 8(3x+7)=2(12x+5) | | 3x-9999= | | 345-23+889x= | | 8+2n-2=8n+6-4n | | 7-24=42 |